2018
DOI: 10.7150/jca.29190
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Survival Outcomes of Breast Cancer with Synchronous Hepatic Metastases: A Population-Based Study

Abstract: Background: Little is known about the clinical features of breast cancer with synchronous hepatic metastases (BCSHM). In this retrospective study, we aimed to feature the incidence and survival outcome of BCSHM.Methods: Data from the 2016 SEER*Stat database (version 8.3.2) was used. The effect of patient and tumor characteristics on the odds of developing of BCSHM was analyzed. Survival was investigated using Kaplan-Meier and Cox regression analyses. A competing risk model was also applied to further investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Because lung metastasis of breast cancer is responsible for a majority of treatment failures [ 64 , [69] , [70] , [71] ], the efficiency of preventing metastasis was also paid great attention. Therefore, we first assessed the direct impact of drug formulations on the metastatic potential of 4T1 cells in vitro .…”
Section: Resultsmentioning
confidence: 99%
“…Because lung metastasis of breast cancer is responsible for a majority of treatment failures [ 64 , [69] , [70] , [71] ], the efficiency of preventing metastasis was also paid great attention. Therefore, we first assessed the direct impact of drug formulations on the metastatic potential of 4T1 cells in vitro .…”
Section: Resultsmentioning
confidence: 99%
“…5 e and S21, both HA-ACVA-AZ NBs and ZPA@HA-ACVA-AZ NBs with AZ could inhibit the expression of CA IX slightly and ZPA@HA-ACVA-AZ NBs + laser induced a more significant decrease of CA IX expression (58.4%), suggesting that suppressing migration of hypoxic 4T1 cells was highly relevant to the down-regulating the expression of CA IX. For in vivo study, lung metastasis is commonly diagnosed at the later stage of breast cancer, which is closely relevant to death in breast cancer [ 49 51 ]. After the tumor inhibition experiment, the lung-metastasized foci in each group were counted (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Married patients may be more active in treating primary tumors, or spouses may urge patients to treat more actively, thus reducing the risk of LM. This also indicated that marital status may affect how cancer patients get access to health services and affect survival time of patients with cancer [17] .…”
Section: Discussionmentioning
confidence: 95%